Imposed Mobility, Legal Ambiguity, Institutionalized Abandonment: Exploring the Sex Work Crimscape in Contemporary Poland - Dziuban, Agata (Critical criminology (Richmond, B.C.), 2024)
When conceptually framed as a crimscape , the contemporary landscape of sex work criminalization can be understood as a complex array of policies relating to sex work, migration, trafficking, fiscality, and labor. Rather than working in isolation, these measures intertwine to shape the working conditions and lived realities of migrant sex workers. Through ethnographic fieldwork and interviews with Ukrainian sex workers in Poland, I demonstrate how this policy assemblage contributes to the vulnerabilization and precarization of migrant sex workers, marking their everyday existence with uncertainty and precarity, surveillance and policing, and the withholding of state protections, recognition, and rights. Analyzing the Polish sex work crimscape as a mode of sex work governance reveals how this policy assemblage translates into three interconnected conditions for migrant sex workers: imposed mobility, legal ambiguity, and institutionalized abandonment.